The sound and the fury: tre sguardi letterari sull’11-S tra rabbia, incredulità e metaletteratura (Altre Modernità, 2011)
The aim of the article is to offer three different versions of the 11-S terrorist attacks, showing how Juan Manuel de Prada (Baracaldo, 1970), Ray Loriga (Madrid, 1967) and Enrique Vila-Matas (Barcelona, 1948) reproduce that tragic event in some of their novels – La vida invisible, El hombre que inventó Manhattan and El Mal de Montano – employing different techniques and approaches. In that way it’s possible to recognize in their pages an interesting spectrum of emotions that goes from rage to refined literary reflections. Still, the analysis of these texts, reveals a subtle uniformity imposed by the television screen: in the contemporary society, images captured by cameras contribute to create a mould that influences the reception of reality and thus causes both a stereotyped assimilation and a sceptical critique of media news. As we will see, precisely that last attitude raises in the authors an hopeless hope of being the witnesses of an unreal event, a sort of paradoxical will to be integrated in the society of the spectacle (Debord) as a psichological defense against horror.
Keywords: 11 settembre 2001; Loriga; Prada; Vila-Matas